Literasi Keuangan Syariah dalam Ruang Hidup Peserta Didik Madrasah Aliyah: Eksplorasi Kontekstual di Polewali Mandar - Muhammad Aslam Ahmad; Nursalim Ahmad; Adrianah, Adrianah (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This study aims to explore the understanding of Madrasah Aliyah students regarding Islamic financial literacy and to identify the supporting and inhibiting factors in their daily lives. Islamic financial literacy is an essential skill for young Muslim generations to make economic decisions in accordance with Islamic principles. Madrasahs, as educational institutions based on Islamic values, play a strategic role in shaping Islamic financial mindsets and behaviors from an early age. This study employs a qualitative approach with an exploratory-contextual method involving students at MA DDI Polewali Mandar. Data were collected through in-depth interviews and field observations. The results indicate that the students' understanding of basic Islamic financial literacy concepts remains relatively low. Generally, students have not fully comprehended fundamental principles such as riba (usury), contracts (akad), zakat (almsgiving), and halal financial practices. Supporting factors include the madrasah environment and religious family backgrounds, while the obstacles are the limited integration of Islamic financial literacy materials into the curriculum and the influence of consumerist media. These findings serve as an initial foundation for designing more practical Islamic financial education strategies within the madrasah environment.